Effect of "IPPON" and "Judo 9+" interventions on balance and coordination in young judo athletes - Naudžiunaite, E.; Aleknaviciute-Ablonske, V.; Bubelis, J. (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija, 2022)
Background. One of the most important skills for judo players is coordination. In judo it is standard to focus more on strength and endurance rather than coordination. Recently coordination of judo players has become a popular topic, and the importance of coordination development has been introduced to researchers. There is a lack of research about the effect of coordination training on balance and coordination changes in judo athletes.